Nekton assemblages in mangrove fringes in Southern Guimaras, Philippines - Malingin, Mary Ann Cielo Lantajo (University of the Philippines Visayas, 2021)
A two and a half year study on the habitat use of nekton assemblages was conducted along the mangrove fringes in the vicinity of Taklong island national Marine Reserve (TINMAR) in Southern Guimaras. Fish corrals with stretched mesh of 20 mm (n=3) facing mon-estuarine mangrove inlets and fringes were smapled weekly for species composition and toher meaurements, while daily catch records from 5 - 8 fish corrals were recorded from march 2011 - September 2013. A total of 319 fish species and 35 invertebrate taxa (=354 taxa) from 96 families and comprising different life stages were recorded. The recorded fish species represent about 10% of the overall number of marine fish species listed in the Philippines. Apogonidae was the most speciose with 27 species, followed by Carangidae and Labridae, each with 19 species. Fish familes Clueidae, Atherinidae, and Apogonidae dominated in terms of numbers, while Plotosidae, Siganidae and carangidae were most abundant in terms of biomass, The most abundant species were Spratelloides gracilis, S. delicatulus, and Atherinomorus doudecimalis in terms of numbers, and Plotosus lineatus, Siganus guttatus and Caranx melampygus in terms of biomass. The most abundant invertebrates were Sepiotheuthis lessoniana (Loliginidae), and Metapenaeus ensis and M. anchistus (Penaeidae) in terms of both numbers and biomass. Autocorrelation and spectral analysis revealed that variability of biomass (kg corral-1 day-1) along mangrove fringes was consistent with lunar periodicity, although correspondence analysis did not show clear correlations between bomass and tidal phase for most common species. This may be attributed to the narrow depth and the resulting to mostly inundated mangrove stands in the study area. Abundance (no. ind), biomass and species richness were higher during the SW monsoon, when juveniles were also more abundant. Seasonal differences between juveniles and adults suggest a relationship to reproductive timing or opportunistic habitat use. Examination of trophic structure showed shifts that agree well with area's temporal nursery function. On the basis of periodicity and seasonality, 20 nekton species (19 fish & 1 cephalopod) were characterized as highly mangrove associated (HMAS) with 5 species represented by juveniles only utilizing the habitat as nursery. About 82% of the biomass of the mangrove associated fauna are from commercially valuable species. this estimate is higher than inferred production of mangrove fisheries in other areas in the Philippines and elsewhere, and clearly signifies the economic importance of resources dependent on mangroves. The high significance of mangroves as nursery and habitat to secondary productivity makes it vital to treat these habitats on equal footing as coral refs in establishing marine protected areas under more robust ecosystem-based management. The results of the study also ndicated a little over 40% of the overall abundance were juveniles, captured in the legal mesh size (20 mm) of the fish corral, thus, it is crucial that the policy on fish corral operation should be reevaluated (increase in mesh size & restriction of no. of gear units) and its prohibition in the nursery habitats in general and within the reserves.